2012
DOI: 10.1074/jbc.m111.299990
|View full text |Cite
|
Sign up to set email alerts
|

Ataxin-3 Regulates Aggresome Formation of Copper-Zinc Superoxide Dismutase (SOD1) by Editing K63-linked Polyubiquitin Chains

Abstract: Background: Polyubiquitination of misfolded proteins is tightly associated with protein aggregation in neurodegenerative disease. Results: Ataxin-3 regulates mutant SOD1 aggresome formation by trimming K63-linked polyubiquitin chains. Conclusion: Deubiquitination by ataxin-3 plays a role in aggresome formation. Significance: Our study provides a previously unrecognized mechanism for the formation of mutant SOD1 aggresomes through the deubiquitination of K63-linked polyubiquitin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 44 publications
3
41
0
Order By: Relevance
“…it is conceivable that polyubiquitin chains including K63-linked chains are progressively modified by deubiquitinating enzymes with time, which could present a confounding factor. Lending support to this, Wang and colleagues [43] recently demonstrated that the formation of aggresomes mediated by mutant superoxide dismutase 1 (SOD1) is dependent on ataxin 3-catalyzed editing of K63-linked polyubiquitin chain on SOD1 (presumably to a correct length). Conversely, knockdown of ataxin-3 decreases mutant SOD1 aggresome formation and increases cell death induced by mutant SOD1.…”
Section: Discussionmentioning
confidence: 99%
“…it is conceivable that polyubiquitin chains including K63-linked chains are progressively modified by deubiquitinating enzymes with time, which could present a confounding factor. Lending support to this, Wang and colleagues [43] recently demonstrated that the formation of aggresomes mediated by mutant superoxide dismutase 1 (SOD1) is dependent on ataxin 3-catalyzed editing of K63-linked polyubiquitin chain on SOD1 (presumably to a correct length). Conversely, knockdown of ataxin-3 decreases mutant SOD1 aggresome formation and increases cell death induced by mutant SOD1.…”
Section: Discussionmentioning
confidence: 99%
“…If the concentration of a certain protein species cannot be controlled by the proteasome, it is sequestered into aggregates, targeted for autophagy (45), and degraded in the lysosome (43). When it comes to the actual handling and molecular environment of the aggregates, this process seems, in turn, to operate at two gears depending on load: either nascent aggregates are cleared directly in the cytosol or if this first line of defense becomes overwhelmed, they are captured in aggresomes for degradation by other more specialized autophagy pathways (43,44). Although the whole-tissue kinetics in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The better option could be to target directly elongation and fragmentation. It is, thus, interesting that the foremost apparent in vivo response to protein aggregation involves sequestration, packing, and coating (38,43,44), all of which are expected to modulate the fibrils' growth dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, JAMMs, a family of DUBs with zinc metalloprotease activity, share the specificity for Lys63‐linked polyubiquitin 34, 35. The Ub editing activity of Josephin ATXN3 is restricted specifically to K63‐linked Ub chains and mixed‐linkage Ub chains 36. Given the fact that DUBs regulate the turnover rate, activation, recycling and localization of multiple proteins, they are central players in governing the signalling pathways and cell homeostasis.…”
Section: Deubiquitylation Enzymesmentioning
confidence: 99%